Measurements of radiocesium in animals, plants and fungi in Svalbard after the Fukushima Daiichi nuclear power plant disaster - Mezaki, Yoshihiro (Heliyon, 2019)
An earthquake struck the eastern part of Japan on March 11, 2011. The Fukushima Daiichi nuclear power plant was severely damaged by the earthquake and subsequent tsunami, leading to the emission of large amounts of radioactive pollutants, including (134)Cs and (137)Cs, into the environment. From August 23 to September 1 in 2011, and from August 27 to September 4 in 2013, we collected samples of animals, plants, fungi and lichens from Svalbard, Norway and measured the radioactivity of (134)Cs and (137)Cs contained in the samples. Though no radioactivity of (134)Cs, which has a half-life of approximately 2 years, was observed, radioactivity of (137)Cs, which has a half-life of approximately 30 years, was observed in some samples of lichens and fungi. We failed to detect the radioactivity of (134)Cs in any of the samples we collected, therefore, it was impossible to say clearly that the radioactivity is derived from Fukushima or not. Nevertheless, the radioactivity data documented in this report are a useful reference for the future surveys of radioactivity within the Arctic.